PERILAKU MAKAN DAN JENIS PAKAN ORANGUTAN (Pongo pygmaeus) DI HUTAN DESA GURUNG MALI KECAMATAN TEMPUNAK KABUPATEN SINTANG - Hardiyansah, Hardiyansah; Prayogo, Hari; Anwari, M Sofwan (JURNAL HUTAN LESTARI, 2019)
The condition of orangutan habitat in ex-situ conservation areas is different from the condition of their natural habitat. These different habitat conditions will have an impact on orangutan behavior, especially food behavior and selection of feed types. This study aims to determine the feeding behavior and the food types of orangutans (Pongo pygmaeus) in the Forest Of Gurung Mali Village Tempunak Sub-district Sintang District. Observation of eating behavior is done using the focal animal sampling method. Observation of eating activities is quantitative, namely recording the time taken during orangutan eating activities. Observation of the type of feed is done by observing the remnants of discarded plants found on the forest floor and trees found as a place for orangutans looking for food sources. Based on observations of the eating behavior of each individual orangutan for the food provided shows the behavior of eating while sitting is higher than the percentage of other eating behavior. For the eating behavior that they are looking for themselves, it shows that Oscar, Digo and Putri tanjung individuals have higher hanging behavior compared to other eating behaviors. The percentage of Momo and Jojo individuals sat higher eating behavior compared to the percentage of other eating behaviors. The types of feed found in the study site were found 8 types of feed provided by the Rehabilitation center and 24 types of natural food contained in the enclosure forest.Keywords : Feeding Behavior, Orangutan, Type of Feed.